Chromosome-Level Genome Assembly of the Rough-Toothed Dolphin (Steno bredanensis) - Haiyu Gao; Hui Kang; Yaolei Zhang; Jiahao Wang; Wenzhi Lin; Peijun Zhang; Mingli Lin; Mingming Liu; Guangyi Fan; Songhai Li (Journal of Marine Science and Engineering, 2023)
The rough-toothed dolphin (Steno bredanensis), the single extant species of the genus Steno, inhabits tropical and subtropical oceans. It is an attractive species for studying aquatic adaptation and evolution. The latest advances in high-throughput sequencing are transforming the study of marine mammals and contributing to understanding various phenomena at the species and population level by determining high-quality genomes. Here, to comprehensively understand the genetic features and explore the molecular basis of aquatic adaption, the chromosome-level genome assembly and comparative genomics analyses of S. bredanensis were performed. The 2.30 Gb final genome assembly of S. bredanensis (scaffold N50 length of 105.53 Mb) was obtained using single-tube long fragment read (stLFR) and Hi-C technologies. The genome assembly clearly revealed the preservation of large chromosomal fragments between S. bredanensis and the melon-headed whale (Peponocephala electra). The S. bredanensis genome contained 19,451 predicted protein-coding genes, of which about 92.33% have functional annotations. The genome assembly and gene sets showed high completeness, with a BUSCO score of 90.6% and 97.3%, respectively. We also identified several positively selected genes specific to S. bredanensis, which may be related to fat cell differentiation, tooth morphogenesis, and immunoregulatory activity. Finally, the demographic dynamics of S. bredanensis were estimated by the pairwise sequentially Markovian coalescent (PSMC) model and found that the population was affected by the climate at the time. We demonstrated that improved continuity and accuracy of the assembled sequence warranted the adoption of this chromosome-level genome as the reference genome and advanced the understanding of genetic features of the rough-toothed dolphin, which will be essential for future evolutionary studies and the protection of this species.